Solitary fibrous tumor of the orbit - Gupta, Sumiti (Asian J Neurosurg, 2016)
Solitary fibrous tumor (SFT) is a rare spindle-cell neoplasm originating from the mesenchyme. It was originally thought to occur exclusively in the intrathoracic region but has been recently described in extrapleural sites including the orbit. SFT of the orbit is a rare lesion, which can be misdiagnosed as hemangiopericytoma, fibrous histiocytoma, meningioma, or neurofibroma. Immunohistochemistry plays an important role. We report an orbital SFT in a 39-year-old female presented with painless, progressive proptosis, and diminished vision in the right eye for the duration of 6 months. Magnetic resonance imaging demonstrated well-defined enhancing mass lesion. The patient underwent complete tumor removal through a right fronto-orbital approach, and a pathological diagnosis of the solitary fibrous tumor was made. Postoperatively, the patient was symptom-free. Clinical and pathological findings including immunohistochemistry are presented along with a brief discussion of literature.